Is there a combined dose-response effect of cigarette smoking and alcohol use during pregnancy on birth weight in a diverse western cape community of South Africa? - Nolan, Heidi (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.